Curve Adjustment Method: Deriving a Formula from a Graph - Mujica, Jose; Mata-Toledo, Ramon A. (American Journal of Management, 2019)
Audio Engineering, and others technical fields, need more mathematical-based methodologies. There are procedures in studio or live recordings that have not been tabulated yet and depend entirely on human experience and appreciation. Audio engineers whether at studios or live-music settings need tools that allow them to translate their daily personal annotations, rules of thumb, live-music and/or empirical experiments into mathematical expressions or formulas that can benefit the practitioners to get rid of the dependency on the personal and individual appreciation. In this paper, the authors attempt to describe a general procedure to convert any group of into a graph.